The battle for Endesa - Rosenthal, Jean W., 1945- (London : SAGE Publications Ltd, 2017)
There were not many lawyers in charge of Europe's largest multinationals, but even among them Wulf H. Bernotat stood out. Now, many years later, as the CEO of Germanys E.ON, Europe's second largest electricity company, Bernotat found himself in one of the most trying battles of his life, one that demanded his entire legal, political, and business savvy. A strong believer in the benefits of fully-liberalized energy markets and industry consolidation, Bernotat had assumed the job as CEO in 2003 with the goal of making E.ON a global energy giant. He had apparently been handed a golden opportunity when Endesa, the leading Spanish electricity firm with substantial holdings in Latin America, was put into play following a takeover bid from Gas Natural, its much smaller, Barcelona-based rival. Endesa's board had rejected the bid outright as too low and had vowed to defend the company's independence. But by the end of the year, it had become clear that Endesa would need a partner to fight off the challenge.
Originally published in Rosenthal, J., & Elias, J. (2016). The battle for Endesa. 102-13. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://cases.advancedmanagement.net/battle-endesa/.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Empresa Nacional de Electricidad (Chile); Empresa Nacional de Electricidad (Peru); Electric utilities -- Latin America